Novel Synthetic-Based Drilling Fluid through Enzymatic Interesterification of Canola Oil - Anawe A. L. Paul; Folayan J. Adewale (International Journal of Chemical Engineering)
Over the years, the oil industries have avoided aromatic, naphthenic, and paraffinic oils as drilling mud base fluids principally because of their detrimental environmental issues on pelagic and benthic marine ecosystems as a result of their toxicity and nonbiodegradability coupled with the possible deterioration of the oil itself and the rubber parts of the drilling equipment because the aromatic hydrocarbons present in the oil have a tendency to dissolve/damage elastomers present in rubber. Hence, possible insights into how to chemically and/or physically produce synthetic base drilling fluids whose cuttings are nontoxic, readily biodegradable, environmentally friendly, and of nonpetroleum source become imperative. In this study, enzymatic interesterification of canola oil was done with ethanol by using enzyme lipase as catalyst under optimum conditions of temperature and pressure and the physicochemical properties of the produced ester were evaluated and compared with that of diesel and a synthetic hydrocarbon base fluid (SHBF). Results show that the specific gravity, kinematic viscosity, dynamic viscosity, and surface tension of canola oil were reduced by 5.50%, 94.74%, 95.03%, and 9.38%, respectively, upon enzymatic interesterification to conform to standard requirements. Similarly, increased |mud ability to pump fluids and possibility of cold temperature environment can be achieved with the reduction in pour point and cloud point, respectively, of the produced canola oil ester. Finally, the produced ester showed no aromatic content as confirmed from its FTIR analysis which indicates its nontoxicity, biodegradability, and environmental friendliness.